Game Theory for Networking Applications - Song, Ju Bin; Li, Husheng; Coupechoux, Marceau (EAI/Springer Innovations in Communication and Computing, 2019)
This book provides recent results of game theory for networking applications. The contributors address the major opportunities and challenges in applying traditional game theory as well as intelligent game theory to the understanding and designing of modern network systems, with emphasis on both new analytical techniques and novel application scenarios. After an overview of game theory for networks, the book narrows in on game theory in communications, game theory in wireless networks, and game theory applications. The book features contributions from researchers and professionals around the world. Presents a variety of perspectives on game theory for networking applications; Shows how game theory can apply to the study of data traffic, new generation networks, and smartgrid; Includes recent results of applied game theory for networks, providing some technical progresses in GAMENETS.